Accuracy of First-Trimester Combined Test in Screening for Trisomies 21, 18 and 13. Issue 11 (November 2017) - Santorum, M.; Wright, D.; Syngelaki, A.; Karagioti, N.; Nicolaides, K. H.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2017;49:714–720) In the last few years, major accomplishments have been made in the screening of trisomies through the development of maternal blood cell-free DNA (cfDNA) analysis. In a previous study, this group published a statistical algorithm used to calculate patient's risks for trisomies 21, 18, and 13 based on patient-specific information obtained from a combined clinical test.